Pendekatan Kesejahteraan Sosial terhadap Anak yang Mengalami Kurangnya Minat Belajar dan Keterampilan Kreatif di Lembaga Kesejahteraan Sosial Anak (LKSA) - Nadiyasa, Mahdiah; Asbi, Erni Asneli; Ritonga, Fajar Utama (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The problem of lack of interest in learning and the suboptimal development of creativity and skills in children is a challenge in efforts to improve children’s social welfare. This study aims to analyze the factors causing these problems and evaluate appropriate social welfare interventions. Using a qualitative case study approach at the Child Welfare Institution (LKSA), this study found that environmental factors, lack of educational stimulation, and minimal access to training were the main causes. Through intervention programs in the form of tutoring, skills training, and creative approaches, an increase in children’s interest in learning and creative abilities was found. The results of this study also show that family environmental factors, past trauma, and minimal educational stimulation contribute to low child motivation. Collaboration is needed between social workers, caregivers, and external parties in supporting holistic child development